Nutritional Composition of Opuntia sulphurea G. Don Cladodes - Carreira, Valeria Paula (2014)
Several studies have shown the interesting properties of Opuntia spp. (“prickly pears”), although most of this knowledge is based on O. ficus-indica. O. sulphurea is a species that is largely distributed in the Monte region of Argentina, where it has been used as an edible resource, especially in periods of food shortage. This is the first report evaluating the chemical composition of O. sulphurea cladodes. Our results show that cladodes are composed primarily of water, as with most other prickly pears that have been studied, which is consistent with their expected role as water reservoir in desert communities. Ash and protein content in O. sulphurea are consistent with values found for other species of the genus, whereas carbohydrates are well below levels of other Opuntia spp. Finally, the percentage of lipids in O. sulphurea cladodes is larger than in other studied species and fatty acid composition is quite different from observations made in similar studies. These earlier studies showed that linoleic acid is the major constituent of fatty acid fractions, followed by palmitic and oleic acids. Our analyses showed that these fatty acids are also principal constituents of O. sulphurea cladodes, although linolenic acid proved to be the most abundant. Curiously, the previous works found relatively low quantities of this fatty acid. Other minor fatty acids were also detected in cladodes of O. sulphurea, although the percentages are larger than in other studies of prickly pears. We discuss our results in the context of the potential nutraceutical and economic utility of O. sulphurea cladodes as a new source of essential fatty acids, especially in semi-arid areas as the Monte region where this species represents an abundant edible resource which is available even in periods of scarcity.